QUARTER-LIFE CRISIS PADA USIA 20 TAHUN KEATAS: TINJAUAN LITERATUR DALAM PERSPEKTIF BIMBINGAN DAN KONSELING - Nofia Lolita; Risma Anita Puriani (CV. Adiba Aisha Amira, 2026)
This study aims to examine the phenomenon of the quarter-life crisis among individuals aged 20 years and above through a literature review from the perspective of guidance and counseling. The issues addressed include the contributing factors, the forms of symptoms that arise, and the role of guidance and counseling services in helping individuals cope with this crisis. The research method used is a literature study with a qualitative descriptive approach by analyzing 20 scientific articles published within the last five years. The results indicate that the quarter-life crisis is influenced by internal factors, such as low self-confidence, unclear life goals, and low resilience, as well as external factors, such as social demands, environmental pressures, and economic instability. The symptoms include anxiety, identity confusion, uncertainty about the future, and emotional instability. From the perspective of guidance and counseling, services such as individual counseling, career guidance, and self-development have been proven effective in helping individuals understand themselves, improve decision-making skills, and plan their future more effectively. Therefore, guidance and counseling play a crucial role in helping individuals navigate the quarter-life crisis in an adaptive manner.